1986
DOI: 10.1016/0749-596x(86)90015-x
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of the stimulus suffix

Abstract: Recall of the final items in a spoken list is hindered by the presentation of a to-be-ignored item. The magnitude of this interference (the stimulus suffix effect) is reduced if the suffix is perceptually distinct from the other list items. Several experiments examine this effect of perceptual distinctiveness. The experiments involve later recognition of stimulus suffixes from lists presented for serial recall. Suffixes which differ from the list items tend to be recognized at least as well as list-similar suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

1989
1989
2006
2006

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
(5 reference statements)
2
7
0
Order By: Relevance
“…Of particular interest is that the difference in the recall and hundred suffix effects was greater at the terminal position (.14) than at the preterminal positions (.05). An ANOVA for just the recall and hundred data showed that the difference between these suffix effects, as expressed in the suffix position interaction, was unlikely to have arisen by chance [F (1,23) 7.01, MS e 0.008, p .01]. This interaction needs to be interpreted with caution, however, since the proportional decrement in the suffix effect obtained with the hundred suffix rounded to 36% at both the preterminal and the terminal positions (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of particular interest is that the difference in the recall and hundred suffix effects was greater at the terminal position (.14) than at the preterminal positions (.05). An ANOVA for just the recall and hundred data showed that the difference between these suffix effects, as expressed in the suffix position interaction, was unlikely to have arisen by chance [F (1,23) 7.01, MS e 0.008, p .01]. This interaction needs to be interpreted with caution, however, since the proportional decrement in the suffix effect obtained with the hundred suffix rounded to 36% at both the preterminal and the terminal positions (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…The 3 (suffix condition) 2 (position) analysis revealed the following: For the main effect of suffix condition, F(2,46) 70.49, MS e 0.015, p .000, and for the main effect of position, F (1,23) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations